[Mes-B-TMP]+ borinium cation initiated cyanosilylation and catalysed hydrosilylation of ketones and aldehydes. Issue 100 (6th December 2021) - Chen, Po-Han; Hsu, Ching-Pei; Tseng, Hsi-Ching; Liu, Yi-Hung; Chiu, Ching-Wen
Abstract : Aryl amino borinium cation can serve as the catalyst for hydrosilylation of ketones and aldehydes. Abstract : Two aryl amino borinium cations derived from Cl(Mes)B-NR2 (NR2 = TMP, HMDS) faced divergent outcomes. As the HMDS-substituted one underwent methyl migration from silicon to boron transforming the putative borinium ion to a silylium ion, [Mes- B -TMP] + can initiate cyanosilylation and catalyse hydrosilylation of ketones and aldehydes.